A Watching Brief at New Court, Trinity College, Cambridge - Rees, Emma (Cambridge Archaeological Unit, Department of Archaeology, University of Cambridge, 2012)
A watching brief was undertaken at New Court, Trinity College, Cambridge between the 11th of July and the 15th of August 2012. Three investigative trenches were excavated by contractors within the northern part of New Court, one of which also extended partway along the adjacent Bakehouse Yard. The trenches were positioned so as to determine the layout and extent of pre-existing services in advance of the proposed instillation of new sewerage and drainage works. This comprised the second phase of investigative work to be undertaken in the area, following on from the insertion of seven similar trenches in December 2011 and January 2012.